Detection of FZD4, LRP5 and TSPAN12 Genes Variants in Malay Premature Babies with Retinopathy of Prematurity - Mohd Khair, Siti Zulaikha Nashwa (J Ophthalmic Vis Res, 2019)
PURPOSE: To determine the mutational analyses of familial exudative vitreoretinopathy (FEVR)-causing genes in Malay patients with retinopathy of prematurity (ROP) to obtain preliminary data for gene alterations in the Malay community. METHODS: A comparative cross-sectional study involving 86 Malay premature babies (ROP = 41 and non-ROP = 45) was performed from September 2012 to December 2014. Mutation analyses in (FEVR)-causing genes (NDP, FZD4, LRP5, and TSPAN12) were performed using DNA from premature babies using polymerase chain reaction (PCR) and direct sequencing. Sequencing results were confirmed with PCR-Restriction Fragment Length Polymorphism (RFLP). RESULTS: We found variants of FZD4, LRP5, and TSPAN12 in this study. One patient from each group showed a non-synonymous alteration in FZD4, c.502C>T (p.P168S). A synonymous variant of LRP5 [c.3357G>A (p.V1119V)] was found in 30 ROP and 28 non-ROP patients. Two variants of TSPAN12, c.765G>T (p.P255P) and c.*39C>T (3′UTR), were also recorded (29 and 21 in ROP, 33 and 26 in non-ROP, respectively). Gestational age and birth weight were found to be significantly associated with ROP (P value < 0.001 and 0.001, respectively). CONCLUSION: Analysis of data obtained from the ROP Malay population will enhance our understanding of these FEVR-causing gene variants. The c.3357G>A (p.V1119V) variant of LRP5, and c.765G>T (p.P255P) and c.*39C>T variants of TSPAN12 could be common polymorphisms in the Malay ethnic group; however, this requires further elucidation. Future studies using larger groups and higher numbers of advanced cases are necessary to evaluate the relationship between FEVR-causing gene variants and the risk of ROP susceptibility in Malaysian infants.